Evaluation of central corneal thickness and corneal topography in children with vernal keratoconjunctivitis - Mohd, Mohd Alif W (2023)
Vernal keratoconjunctivitis (VKC) is a chronic allergic disease characterised by intense ocular surface symptoms and corneal involvement. We aimed to compare the central corneal thickness (CCT) and corneal topography changes between children with VKC and healthy children, as well as among the different groups of severity of VKC. Materials and Methods This study is a comparative, cross-sectional, hospital-based study. We recruited 86 children with VKC and 86 healthy children as controls. All participants underwent complete ocular examinations, including CCT using an ultrasound pachymeter and corneal topography using a placido disc corneal analyser. Data from the right eye were analysed. Results There was a statistically significant reduction in mean CCT in children with VKC compared to controls (p < 0.05). The mean CCT was observed to be thinnest in the severe-very severe groups of VKC (533.09 ± 10.52 μm) compared to the mild-moderate (546.79 ± 12.52 μm) and control groups (546.59 ± 12.17 μm) (p < 0.05). Almost all cornea topographic indices including simulated keratometry 1 and 2 (sim K1, sim K2), apical keratometry, apical gradient curvature (AGC), superior-inferior index, keratoconus prediction index (KPI), and percent probability keratoconus (PPK) were noted to be significantly higher in severe-very severe VKC compared to mild-moderate VKC and controls (p < 0.05). However, there was no significant difference in cylinder value when comparing different groups of severity of VKC (severe-very severe 1.31 ± 0.90 diopters (D), mild-moderate 1.33 ± 1.42 D; p = 0.91). Conclusion The severe-very severe VKC group had significantly thinner CCT and higher values in corneal topographic indices compared to the mild-moderate VKC group and the controls group. Astigmatism was not statistically different among the different severities of VKC.